CHALLENGES FACED BY COMMUNITY WORKERS DEALING WITH FLOOD VICTIMS IN PAKISTAN, 2022 - Liaqat, Summaira; Anjum, Fareeha; Riaz, Samina; Batool, Maryam (Journal of Arts & Social Sciences, 2024)
A qualitative exploration of gender-based challenges encountered by male and female community workers engaged in disaster response, specifically focusing on their roles in assisting the victims of the 2022 flood in Pakistan. The study employs an interview-based methodology to capture the nuanced experiences and perspectives of these community workers. Through semi-structured interviews, the research reveals distinct gender-specific challenges faced by male and female community workers. Male participants grapple with logistical and coordination obstacles, compounded by resource constraints and personal commitments. Health and well-being concerns are exacerbated by unsanitary conditions in disaster-affected areas. In contrast, female community workers contend with stigma, cultural barriers, and the delicate balance of providing psychological support. Additionally, they shoulder the responsibility of child-centred engagement and addressing gender-specific needs. The findings underscore the imperative of gender-sensitive disaster response strategies. Recognizing and addressing these gender-based challenges is essential for fostering inclusive and effective disaster relief efforts. By leveraging the insights derived from this study, policymakers and practitioners can formulate targeted interventions that acknowledge and cater to the distinct roles and responsibilities of male and female community workers in times of crisis.